Three-Dimensional Modeling of Anode-Supported Planar SOFC with Corrugated Electrolyte. Issue 10 (4th October 2021) - Liu, Pengwei; Fan, Shengliang; Liu, Yang; Han, Xu; Jin, Zunlong
Abstract : The aim of this work is to analyze the effect of corrugated electrolyte on the cell performance. The corrugated electrolyte is applied to the traditional anode-supported planar solid oxide fuel cell (SOFC) based on the theory of mesoscale electrode-electrolyte interface modification. Three-dimensional models of SOFCs with electrolytes with different corrugation heights and periods are developed. In order to better understand the influence mechanism of corrugated electrolyte, not only the effect of the corrugated electrolyte on the overall cell performance is analyzed, but also the local gas distribution, concentration polarization, activation polarization, exchange current density and electron current density are discussed. The results show that the corrugated electrolyte leads to a decrease in the local exchange current density, but the enlargement of the activation reaction zone leads to an increase in the total charge transfer, thereby resulting in an improvement in cell performance. The enhancement of average current density with an expansion factor of 2 has a maximum value of 56.9% at an operating voltage of 0.7 V.